All small molecule ternary organic photovoltaic with two well compatible nonfullerene acceptors for minimizing energy loss. (15th January 2021) - Liu, Zhiyong; Wang, Ning
Highlights: The ternary OPVs with blend acceptor achieved a PCE of 13.85%. Around 10% PCE improvement is obtained by employing ternary strategy. The improvement of exciton dissociation at the BTR/MeIC/Y11 interface. The enhancement of photon harvesting by the blend acceptor of MeIC and Y11. Abstract: A ternary strategy (BTR as donor, Y11 as host acceptor and MeIC as guest acceptor) was employed to realize a high performance ternary SMPVs. A high PCE of 13.85% was achieved for an optimized ternary SMPVs with 30 wt% MeIC in acceptors. An approximate 10% improvement in the PCE was realized by employing ternary strategy in comparison with that of BTR:Y11 binary SMPVs, which was attributed to a significantly increased J SC despite a slightly decreased V OC and FF. The similar LUMO energy levels of Y11 and MeIC are beneficial for efficient electron transfer and avoid the introduction of charge recombination centers into the ternary photoactive layers. The MeIC exhibits complementary absorption spectra between BTR and Y11, which should be beneficial towards enhancement of photon harvesting ability of ternary photoactive layers, leading to high J SC value. The all small molecule ternary strategy with MeIC as guest acceptor shows an broaden light absorption region, cascade energy level alignment and appropriate phase separation and surface morphology for realizing an efficient ternary SMPVs.